Spatial distribution and influencing factors of villages and towns with characteristic industries in China(中国乡村特色产业村镇空间分布及影响因素) - 李练练(LI Lianlian); 陈国磊(CHEN Guolei); 张纪莎(ZHANG Jisha); 马太佳(MA Taijia); 吴学成(WU Xuecheng) (Zhejiang Daxue xuebao. Lixue ban)
Promoting industrial prosperity is the primary task of implementing the rural revitalization strategy. Taking villages and towns with rural characteristic industries in China from 2020 to 2022 as the research object, the spatiotemporal characteristics and influencing factors of rural characteristic industry villages and towns were analyzed by using the methods such as nearest proximity index, kernel density estimation, spatial autocorrelation analysis, geographic detector and other spatial analytic methods. The results show that: The villages and towns with rural characteristic industries exhibit an overall excessive agglomeration in space, with a spatial distribution trend of "dense in the southeast of China, sparse in the northwest" and "cold in the west and hot in the east"; The population and transportation facility have the strongest influence on the spatial distribution, while the influence of the land resources is the weakest; The interaction detection results of influencing factors show a dual factor enhancement or non-linear enhancement, with the strongest interaction effect between population size and economic development level.(推进产业兴旺是实施乡村振兴战略的首要任务，以2020—2022年中国乡村特色产业产值超十亿元镇和超亿元村为研究对象，运用最近邻指数法、核密度估计法、空间自相关分析法、熵值法、地理探测器等方法，分析乡村特色产业村镇的时空格局演化特征及影响因素。结果表明：乡村特色产业村镇在空间上呈过度集聚，并呈现“东南密西北疏”“西冷东热”的分布态势；乡村特色产业村镇空间分布格局受人口数量、交通运输能力的影响显著，受土地资源的影响较弱；影响因素的交互探测结果呈双因子增强或非线性增强，其中人口数量与经济发展水平的交互影响最强。)